ADMINISTRASI KELOMPOK WANITA TANI (KWT) DI KECAMATAN TOMOHON SELATAN KOTA TOMOHON - Margaretha Mariska Mamesah; Benu Olfie. L. S; Jenny ., Baroleh (AGRI-SOSIOEKONOMI, 2017)
This study aims to determine the administrative completeness of women farmer groups inTomohon Selatan Subdistrict Tomohon City. This study was conducted from January to March 2017. Thedata used are primary data obtained from direct interviews with women farmer group organizations(Chief, Secretary, Treasurer) based on a prepared list of questions. The analysis used for theadministrative variable of activity and financial administration that is each answer is related to the formof statement which is expressed with the words that is Good given Score: 3, Less Good is given Score: 2and Not Good is given Score: 1. Result of research indicate that administration activity in Seruni andfarmer group of Kemangi are complete while Flower is not complete. Seruni and Kemangi categorizedgood because 80% of books exist and complete filled and 20% was not complete, while group of farmerof Flower is categorized not good because only 60% book filled with complete and 40% of the otheradministrative books are not exist. The Finance Administration of the three groups of women farmers iscategorized as unfavorable because only 50% of the books are available and are completed by the womenfarmer group.